KAPASITAS INFILTRASI PADA BERBAGAI TEGAKAN DI HUTAN PENDIDIKAN WANAGAMA I GUNUNG KIDUL - , PRATAMA BAGUS KURNIAJI, Dr. Ir. Ambar Kusumandari, M.E.S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Wanagama I is an educational forest that was built at critical land. The success of developing forest create a big improvement with at least 13 stands were established. Wanagama I at the beginning was an area covered by stone and little soil but it has 20-80 cm of soil layer now. The improvement will influence the hydrological cycle in Wanagama I. One of the components is soil infiltration capacity as a success parameter of developing forest.The purpose of this research is to measure and compares the infiltration capacity of various stands and an empty land in Wanagama I and assesses the use of two different methods : the single ring and double ring infiltration method. The single ring and double ring infiltration method was applied to measure the infiltration capacity. The characteristic of vegetation and soil was collected to compare the characteristics of stand. The assessment of two different methods were analyzed by Wilcoxon analysis. The result showed that Wanagama I has 13 types of stand with wide range of infiltration capacity. The 13 stands consist of Swietenia macrophylla with 0.04cm/hour infiltration capacity, Eucalyptus pellita 0.40 cm/hour, Melaleuca cajuputi 0.06 cm/hour, Diospyros celebica 0.08 cm/hour, Gmelina arborea 0.8 cm/hour, Eucalyptus alba 4.00cm/hour, Eucalyptus urophylla 0.08 cm/hour, Acacia mangium Willd. 0.1 cm/hour, Pinus merkusii 0.4 cm/hour, Acacia crassicarpa 0.2 cm/hour, Tectona grandis 0.15 cm/hour, Acacia auriculiformis 0.1cm/hour and empty area 0.4 cm/hour. The biggest capacity owned by Cassia siamea 6.0 cm/hr. The Wilcoxon analysis result shows 0.279 of significant number means thereâs no significant different.